Socio-economic and agricultural factors associated with stunting of under 5-year children: findings from surveys in mountains, dry zone and delta regions of rural Myanmar (2016-2017) - Min Kyaw Htet; Tran Thanh Do; Thet Wah; Thant Zin; Myat Pan Hmone; Shahreen Raihana; Elizabeth Kirkwood; Lwin Mar Hlaing; Michael J Dibley (Cambridge University Press, 2023)
Abstract Objective: The study's objective was to investigate multiple underlying social, economic and agricultural determinants of stunting among under-five children in three distinct ecological areas in rural Myanmar. Design: Repeated cross-sectional surveys in three states of Myanmar. Setting: Rural households in Chin (mountainous), Magway (plains) and Ayeyarwady (delta). Participants: From two purposively selected adjacent townships in each state, we randomly selected twenty villages and, in each village, thirty households with under-five children. Households in the first survey in 2016 were revisited in late 2017 to capture seasonal variations. Results: Stunting increased from 40·4 % to 42·0 %, with the highest stunting prevalence in Chin state (62·4%). Univariate Poisson regression showed factors contributing to child stunting varied across the regions. Adjusted Poisson regression models showed that child's age and short maternal stature (aRR = 1·14 for Chin, aRR = 1·89 for Magway and aRR = 1·86 for Ayeyarwady) were consistently associated with child stunting across three areas. For Chin, village-level indicators such as crop consumption (aRR = 1·18), crop diversity (aRR = 0·82) and land ownership (aRR = 0·89) were significantly associated with stunting. In Magway, the number of household members (aRR = 1·92), wealth status (aRR = 0·46), food security status (aRR = 1·14), land ownership (aRR = 0·85) and in Ayeyarwady, women's decision-making (aRR = 0·67) and indicators related to hygiene (aRR = 1·13) and sanitation (aRR = 1·45) were associated with stunting. Conclusions: Area-specific factors were associated with stunting. Maternal short stature and child age were consistent determinants of stunting. A multi-sectoral local approach, including improvements in transport, is needed to address the intergenerational malnutrition problem.